Concerns regarding the effects of the COVID19 pandemic on children health (One Health & Risk Management, 2021)
Introduction. The unexpected situations (lockdown, online school, social distancing) imposed to stop the spreading of the coronavirus COVID19 starting with March 2020 in most of the worldwide countries brought collateral effects for every citizen. Now, after more than a year, became a certitude that one of the most affected categories were the children, because of the restrictions and online school, that disrupted their habits. The concerns regarding the way are affected their physical and psychical development and health are growing between the researchers, as long as in many countries the restrictions are still in force. Also, there are big differences between countries, and even between regions of the same country about how strongly these restrictions are applied, meaning that discriminations occurred even more.This article will reinforce the evidence on the risks for children's health and development due to pandemic restrictions on social interaction and education, based on the case of children from Bucharest. Starting from the conclusions of a literature review on these issues will be emphasized the conclusions of researchers from different countries regarding the main concerns about children's health.Material and methods. For completing the image referring to these risks, will be analyzed the results of a quantitative research conducted with parents and their children from gymnasium school in Bucharest regarding the way they perceive how the pandemic restrictions changed their habits. Because for these children (from Bucharest) coming to school is still forbidden after more than one year (meaning 90% of the last one and a half school year was online) the research methods were also online, using questionnaires created and applied through Google forms. No sample methods could be applied (the questionnaire link was sent to all the parents with children of 11-14 years old from this school) and about 40% of them responded, pair parents-child.Results. Th results showed that there is evidence that doing school online, not only the efficiency of learning is affected, but through the increase of time spent using the internet, their health and development are at risk. Issues like sedentarism, obesity, vision and eye or posture, and spine problems increase, being doubled by the psychical and mental impairment: stress, isolation, anxiety, depression, lack of attention and concentration, and increasing in cyberbullying and other online risks for children. The results showed that there is a need that the researchers, parents, and teachers’ parts to keep a balance between keeping children (and their families) safe from coronavirus through restrictions and the negative collateral effects on their health and development that might affect them on the medium and long term. Conclusions. The analysis showed that there are differences between parents and children's perceptions of the collateral effects of the pandemic on children's health and development, both on physical and psychical, mental level. Even this research study is limited and lacks statistical representativeness, through comparative analysis and cumulating this research results with the others at the international level, will be revealed and enhanced once more the fact that the collateral effects of pandemic and the social restrictions are real, and could have a meaningful negative impact on children development and health, on a long term.